Um teto todo nosso: memória, solidariedade e as mulheres que constroem as cidades em mutirões autogeridos - Silva, Jéssica Idalina Ribeiro da (2024)
The research is conducted by recovering the memories of women about their collective experiences as builders of the city. This work aims to present the stories of active participation of two generations of women in the construction and part of the Garras eLutas housing complex, developed by CDHU—the first self-managed housing project in the Brasilândia region during the 1990s. The investigation focuses on the fact that, beyond building their own homes, these women established social solidarity ties over the years. It highlights how the strengthening of these bonds was crucial for community survival and organization. These relationships are analyzed not through the lens of financial or state deficiencies but as a way in which they invent and reinvent survival strategies. This political activism in the fight for dignified housing led to the creation of a living, organized, and caring community, which continued even after each woman had secured her own home. The theoretical foundation is based on feminist epistemologies, with ethnography, feminist empiricism, and in-person semi-structured interviews with some of the women who participated in the Garras e Lutas construction serving as the methodology